Application of Computer Assisted Inatruction (ACI) For Helping Primary Teachers In Teaching of Indonesia Culture - Yulianto, Budi; Layona, Rita (Teknik dan Ilmu Komputer, 2015)
AbstrakÃÂ Metode pengajaran yang menerapkan Computer Aided/Assisted Instruction (CAI) telah mendukung pembelajaran yang lebih menarik dan efektif, khususnya bagi guru dan siswa sekolah. Penelitian sebelumnya menunjukkan bahwa CAI membantu guru dalam menyampaikan materi dan membantu siswa dalam memahami materi dengan lebih baik, serta memberikan pengaruh positif terhadap hasil belajar siswa. Penelitian ini bertujuan untuk menerapkan CAI pada metode pembelajaran pada siswa sekolah dasar. Hasil dari penelitian ini berupa perangkat ajar CAI dengan mata pelajaran kebudayaan Indonesia pada sekolah dasar dengan memadukan gambar, tulisan, suara, serta latihan atau kuis. Metodologi perancangan menggunakan rational unified process yang meliputi tahapan business modelling, requirements, analysis and design, implementation, test, dan deployment. Kesimpulan yang didapat dari penelitian ini, yaitu aplikasi perangkat ajar CAI dapat membantu guru dalam menyampaikan materi dengan lebih menarik, membantu siswa memahami materi, serta adanya soal latihan sebagai evaluasi terhadap hasil pembelajaran siswa.ÃÂ Kata kunci: metode pengajaran, computer aided instruction, computer assisted instruction, CAI, rational unfied process, kebudayaan IndonesiaÃÂ ÃÂ AbstractÃÂ Teaching method that implements Computer Aided/Assisted Instruction (CAI) has made learning more interesting and effective, especially for teachers and students. Previous research has suggested that CAI helps teachers in delivering learning materials and students in understanding the materials better. ÃÂ CAI consequently gives positive impact to student learning outcomes. The goal of this research is to implement CAI as a teaching method in primary schools. The research output is a CAI based teaching tool for the Indonesian Culture lesson by combining images, texts, sounds, and exercises or quizzes for elementary schools. The methodology development uses a rational unified process that contains business modeling, requirements, analysis and design, implementation, test, and deployment. The study concludes that the CAI based teaching tool can assist teachers in delivering the material more interestingly, help students understand the material, and also implement exercises for student learning outcomes evaluation.ÃÂ Keywords: teaching method, computer aided instruction, computer assisted instruction, cai, rational unfied process, indonesia culture